Opinion evidence in cell site analysis. Issue 4 (July 2020) - Tart, Matt
Highlights: The Case Assessment and Interpretation (CAI) Model applied to Cell Site Analysis. A case example is presented. Differences between alternative interpretive approaches are highlighted.